2015
DOI: 10.1111/gbb.12226
|View full text |Cite
|
Sign up to set email alerts
|

COMT polymorphism modulates the resting‐state EEG alpha oscillatory response to acute nicotine in male non‐smokers

Abstract: Performance improvements in cognitive tasks requiring executive functions are evident with nicotinic acetylcholine receptor (nAChR) agonists, and activation of the underlying neural circuitry supporting these cognitive effects is thought to involve dopamine neu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 170 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…A more recent study [55] investigated the modulatory role of the COMT genotype on nicotine effects in resting-state condition in nonsmokers. They found an increase in upper α power frontocentrally in Met/Met carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study [55] investigated the modulatory role of the COMT genotype on nicotine effects in resting-state condition in nonsmokers. They found an increase in upper α power frontocentrally in Met/Met carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the COMT genotype seems to be important in determining the individual response to nicotine [55]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that while muscarinic blockers like scopolamine diminish the resting parieto-occipital alpha oscillations (Sannita et al, 1987 ; Sloan et al, 1992 ; Ebert et al, 1998 , 2001 ; Kikuchi et al, 1999 ; Osipova et al, 2003 ; Ramos Reis et al, 2013 ), nicotinic administration produces the reverse effect (Gilbert et al, 2000 ; Knott et al, 2000 , 2012 ; Walker et al, 2001 ; Bowers et al, 2015 ; Smith et al, 2016 ) but see (Knott and Fisher, 2007 ; Balsters et al, 2011 ; Fisher et al, 2012b ). Acetylcholine enhancers tend to increase posterior alpha power during visuospatial attentional modulations (Bauer et al, 2012 ) Figure 1c and frontal alpha during working memory tasks (Fisher et al, 2012a , 2013 ) but see (Eckart et al, 2016 ).…”
Section: Parieto-occipital Alpha Oscillations Are Modulated By a Myrimentioning
confidence: 99%
“…The EO condition was considered ideal for testing the effect of nicotine, because nicotine appears to target attentional networks [13,14]. The EC condition was also considered important since nicotine impacts this condition as well [15]. Lastly, a mixed-effects design was employed in which subjects were randomly allocated to a drug or placebo and each subject was tested before and after their administration.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to investigate 3 frequency bands in accordance with the previous literature about EEG and nicotine during EO and EC activity [15,18,19]. The selected frequency bands used here were: α 1 , 8.5-10.4 Hz; α 2 , 10.5-12.4 Hz, and β 1 , 12.5-18.4 Hz.…”
Section: Introductionmentioning
confidence: 99%